Spectroscopic methods for nanomaterials characterization - Thomas, Sabu; Thomas, Raju; Zachariah, Ajesh K. 1983-; Mishra, Raghvendra Kumar (Amsterdam Elsevier, 2017)
Nanomaterials Characterization Techniques, Volume Two, part of an ongoing series, offers a detailed analysis of the different types of spectroscopic methods currently being used in nanocharacterization. These include, for example, the Raman spectroscopic method for the characterization of carbon nanotubes (CNTs). This book outlines the different kinds of spectroscopic tools being used for the characterization of nanomaterials and discusses under what conditions each should be used. The book is intended to cover all the major spectroscopic techniques for nanocharacterization, making it an important resource for both the academic community at the research level and the industrial community involved in nanomanufacturing.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nanostructured materials -- Spectra; Spectrum analysis -- Methodology; Electronic books